2012
DOI: 10.1371/journal.pone.0041028
|View full text |Cite
|
Sign up to set email alerts
|

Ultramarine, a Chromoprotein Acceptor for Förster Resonance Energy Transfer

Abstract: We have engineered a monomeric blue non-fluorescent chromoprotein called Ultramarine (fluorescence quantum yield, 0.001; ε 585 nm, 64,000 M−1. cm−1) for use as a Förster resonance energy transfer acceptor for a number of different donor fluorescent proteins. We show its use for monitoring activation of caspase 3 in live cells using fluorescence lifetime imaging. Ultramarine has the potential to increase the number of cellular parameters that can be imaged simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…The dark yellow REACh [15] and intense blue Ultramarine [17] are reported to be suitable acceptors for the emission of EGFP. However, use of such dark acceptors to monitor FRET requires donor fluorescence emission lifetimes to be determined using sophisticated and expensive instrumentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dark yellow REACh [15] and intense blue Ultramarine [17] are reported to be suitable acceptors for the emission of EGFP. However, use of such dark acceptors to monitor FRET requires donor fluorescence emission lifetimes to be determined using sophisticated and expensive instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of such multi-parameter experiments is limited by the number of different FPs whose emission can be separately detected. Although the availability of non-fluorescent genetically encoded acceptors such as REACh [15], [16] or Ultramarine [17] has the potential to increase the number of separate events that might be monitored in the same experiment, access to expensive instrumentation is required to determine fluorescence lifetimes and FRET.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the FRET from mRuby2 to dark mCherry mutants was taking place. Furthermore, we paired Ultramarine, which is a known dark fluorescent protein12, with mRuby2, and found that FRET also occurs in the mRuby2-Ultramarine pair (Fig. 2c,d).…”
Section: Resultsmentioning
confidence: 96%
“…Notably, because such pairs require only a narrow range of wavelengths (550–650 nm), they facilitate dual observation with a green fluorescent dye or protein using the 500–550 nm range of wavelengths (Figs 3 and 4). Although chromoprotein named Ultramarine was reported as an acceptor for FLIM-FRET, and its spectral properties are similar to those of dark mCherrys12, the reduced cell-to-cell variability of dark mCherrys represents a big advantage over Ultramarine (Fig. 2e).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation